Urban energy transition between regulatory evolution and scientific production: a bibliometric analysis - Martinelli, Valerio (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. This section, International Regulations and Legislation for the Energy Transition, explores the challenges and opportunities in the urban context to understand the evolving landscape of the global energy transition. The contribution explores how scientific research on urban energy transition has evolved alongside European climate policies. It highlights the role of urban governance and planning in supporting decarbonisation through tools like Positive Energy Districts and Renewable Energy Communities. These models integrate innovation with citizen engagement and local energy autonomy. The analysis also reveals how regulatory developments have shaped research priorities. Finally, it underscores the need for stronger coordination to overcome implementation gaps.